El coral de la Novena sinfonía de Beethoven y su relación con el lied Gegenliebe y la Fantasía para piano, coro y orquesta del mismo compositor - Kansumanht Schiaffino, Karla Yvonne (2023)
The present research deals with the Chorale of the fourth movement of Beethoven’s Ninth Symphony, for which the source of the musical idea is sought and takes shape, based on references related firstly to the second lied Gegenliebede the secular cantata Seufzer eines Ungeliebten - Gegenliebe WoO 118, composed by a young Beethoven. The second reference is the Fantasy for piano, choir and orchestra in C minor, op. 80, composed when Beethoven was 38 years old. This work has a similarity with the fourth movement of the Ninth Symphony by the same composer, both in the themes and in the musical ensemble in general, especially with the jubilant entrance of the choir’s “Ode to Joy”. An analysis of the three works is made of both the texts of the poets Bürger and Schiller, as well as the vocal, choral and instrumental music that gave birth to the choral symphony in Beethoven’s Ninth.